Weaning from mechanical ventilation: a narrative review - Cristian Fusi; Enrico Bulleri; Giulia Azzini (Firenze University Press, 2022)
The "weaning" from mechanical ventilation is a process that involves several assessments and steps to aid a patient to reach a "liberation" from the ventilator and allow for breathing autonomy. The process of "weaning" from mechanical ventilation involves several assessments and steps to support a patient in reaching a "liberation" from the ventilator and allow for spontaneous breathing. The weaning process consists of evaluating if the patient is able to breathe with minimal or no ventilation support. This assessment is performed by a diagnostic test named spontaneous breathing trial (SBT), repeated every 24 hours to ensure extubation success. Even though many patients do not meet the eligibility criteria for starting the weaning process, they can still be weaned. For this reason, these criteria should be evaluated in order to assess a possible weaning, rather than adopting absolute standards which have to be met simultaneously. The SBT helps the healthcare professionals to understand the patient's capacity to sustain physiological breathing once they are extubated (or on spontaneous breathing if a tracheostomy tube is maintained in place). Several patients fail to meet the weaning criteria after less than 20 minutes of the SBT. Therefore, a 30-minute trial is enough to estimate the patient's capacity to withhold spontaneous breathing.  Even if the SBT is currently the gold standard method to conduct the weaning trial, it does not prevent the occurrence of complications after extubation such as upper airways obstruction, increased resistance, loss of airway protective reflexes, cough efficiency, and drainage of tracheobronchial secretions. The preventive use of NIV or High Flow Nasal Cannula is strongly recommended for patients experiencing extubation failure and mechanically ventilated for more than 24 hours after an SBT.  A well-performed SBT usually leads to definitive extubation; on the other hand, SBT failure requires a comprehensive investigation on potentially reversible conditions. Prolonged weaning is highly wasteful in terms of time and resources due to the need for a systematic and multidisciplinary approach to successfully face the weaning process.